2017
DOI: 10.1053/j.gastro.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Activates YAP and a Positive-Signaling Loop to Promote Colon Regeneration After Colitis but Also Carcinogenesis in Mice

Abstract: BACKGROUND & AIMS Prostaglandin E2 (PGE2) is mediator of inflammation that regulates tissue regeneration, but its continual activation has been associated with carcinogenesis. Little is known about factors in the PGE2 signaling pathway that contribute to tumor formation. We investigated whether yes associated protein 1 (YAP1), a transcriptional co-activator in the Hippo signaling pathway, mediates PGE2 function. METHODS DLD-1 and SW480 colon cancer cell lines were transfected with vectors expressing transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 46 publications
7
78
1
Order By: Relevance
“…In fact, a growing body of research has suggested that Yap nuclear translocation is unlikely to fully explain the role of Yap in cancer development [50, 51] and that Yap nuclear localization accounts for only a small portion of cancer progression [22]. Additionally, several studies have confirmed that the mRNA levels of Yap (and TAZ) sufciently correlate with target gene expression and are significantly associated with cancer progression [7, 23]. Meanwhile, an increasing number of studies have also shown that Yap has the ability to interact with tumor suppressors in the cytoplasm [52], supporting the idea that excessive expression of Yap is actually a more important factor in tumorigenesis regardless of Yap nuclear localization or cytoplasmic retention [7, 8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, a growing body of research has suggested that Yap nuclear translocation is unlikely to fully explain the role of Yap in cancer development [50, 51] and that Yap nuclear localization accounts for only a small portion of cancer progression [22]. Additionally, several studies have confirmed that the mRNA levels of Yap (and TAZ) sufciently correlate with target gene expression and are significantly associated with cancer progression [7, 23]. Meanwhile, an increasing number of studies have also shown that Yap has the ability to interact with tumor suppressors in the cytoplasm [52], supporting the idea that excessive expression of Yap is actually a more important factor in tumorigenesis regardless of Yap nuclear localization or cytoplasmic retention [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have confirmed that the mRNA levels of Yap (and TAZ) sufciently correlate with target gene expression and are significantly associated with cancer progression [7, 23]. Meanwhile, an increasing number of studies have also shown that Yap has the ability to interact with tumor suppressors in the cytoplasm [52], supporting the idea that excessive expression of Yap is actually a more important factor in tumorigenesis regardless of Yap nuclear localization or cytoplasmic retention [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTGS2 is a key step in the production of prostaglandin E2 (PGE2) in cancer cells, which plays important roles in modulating motility, proliferation and resistance to apoptosis. 25 This down-regulation was found in ADME, signal transduction, cardiovascular disease and inflammation families.…”
Section: Discussionmentioning
confidence: 96%